The impacts of liner shipping connectivity and economic growth on international trade case of european countries and Turkey - Seker, Ayberk (IGI Global, 2022)
Sea transportation and maritime transport networks have commonly been used with the development of international trade. Maritime transportation is more widely used for the transportation of high-volume cargoes in international trade particularly, since sea transportation is cheaper and safer than road and railway transportation. This chapter investigates the relationship among exports, liner shipping connectivity index, and economic growth in European countries and Turkey. Analysis found that liner shipping connectivity index and economic growth have a positive effect on the exports in European countries and Turkey. It is revealed that 1% increase in liner shipping connectivity index provides the increment 0.21% in the exports. In addition, 1% increment in gross domestic product ensures the increase 1.05% in the exports. © 2023 by IGI Global. All rights reserved.